Efficient Removal of Lead and Chromium From Aqueous Media Using Selenium Based Nanocomposite Supported by Orange Peel - Aziz, Maria; Aziz, Rukhsanda; Rafiq, Muhammad Tariq; Abbasi, Maryam; Taneez, Mehwish; Azhar, Muhammad Usman; El Askary, Ahmad; Elesawy, Basem H.; Eed, Emad M.; Khalifa, Amany S.; Qayyum, Abdul (Frontiers in Environmental Science, 2022)
This study presents the synthesis of activated orange peel, derived from bio-waste (orange peel) and its doping with selenium nano-particles to enhance the adsorption capacity. The synthesized nanocomposite orange peel/Selenium (OP/Se) was applied as adsorbents for the removal of Lead (Pb) and Chromium (Cr) from synthetic waste water as an economical water cleaning technology. Orange peel/Selenium nanocomposite was characterized by X-Ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and Scanning electron microscopy (SEM). Scanning electron microscopy results showed the porous structure of OP/Se nanocomposite and distinct peaks observed in XRD and FTIR spectra depicted the successful synthesis of nanocomposite. Batch experiments were conducted to figure out the effect of different parameters on adsorption of Pb and Cr by using Atomic Absorption Spectroscopy. The maximum adsorption capacity of 99.9% was achieved for both lead and chromium at acidic pH. While at temperature of 60⁰C the maximum adsorption of 98.3% and 95.9% was found for Pb and Cr respectively. Kinetics followed the pseudo 2nd order which indicated the chemisorption mechanism in adsorption process. Adsorption isotherms indicated that the equilibrium data fits well with Langmuir isotherm model in the process of adsorption. The adsorption thermodynamics indicate that adsorption of heavy metals ions is spontaneous (ΔG°<0) and the adsorption increases with increase in temperature which means that reaction was endothermic. This study revealed that the synthesized bio-activated nanocomposite was an efficient adsorbent material for the removal of heavy metals from waste water.